Sporadic Creutzfeldt–Jakob disease with glial PrPRes nuclear and perinuclear immunoreactivity. Issue 5 (19th August 2018) - Fernández‐Vega, Ivan; Díaz‐Lucena, Daniela; Azkune Calle, Itxaso; Geijo, Maria; Juste, Ramon A.; Llorens, Franc; Vicente Etxenausia, Ikerne; Santos‐Juanes, Jorge; Zarranz Imirizaldu, Juan Jose; Ferrer, Isidro
Abstract : Proteinase K‐resistant prion protein (PrP Res ) nuclear and perinuclear immunoreactivity in oligodendrocytes of the frontal cortex is found in one case of otherwise typical sporadic Creutzfeldt‐Jakob disease (sCJD) type VV2a. The PrP nature of the inclusions is validated with several anti‐PrP antibodies directed to amino acids 130–160 (12F10), 109–112 (3F4), 97–102 (8G8) and the octarepeat region (amino acids 59–89: SAF32). Cellular identification and subcellular localization were evaluated with double‐ and triple‐labeling immunofluorescence and confocal microscopy using antibodies against PrP, glial markers, and histone H3. Based on review of the literature and our own experience, this is a very odd situation that deserves further validation in other cases.